Relative antigenicity of components in vascularized composite allotransplants: An experimental study of microRNAs expression in rat hind limb transplantation model. Issue 4 (17th December 2018) - Oda, Hiroki; Ikeguchi, Ryosuke; Aoyama, Tomoki; Ohta, Souichi; Noguchi, Takashi; Kaizawa, Yukitoshi; Yurie, Hirofumi; Takeuchi, Hisataka; Mitsuzawa, Sadaki; Yamamoto, Koji; Matsuda, Shuichi
Abstract : Background: Skin is considered to be the most antigenic component of all vascularized composite allotransplantation tissues. However, no studies have used methods other than histological assessment to analyze the relative antigenicity of various components. In this study, we analyzed gene expression to investigate the relative antigenicity of each component in the transplanted limb. Methods: Seven Brown Norway rats and 31 Lewis rats were assigned to two groups: an allograft group and a syngeneic (control) group. Brown Norway rats were used as the allogeneic donors, and Lewis rats were used as the syngeneic donors and recipients. About 13 recipients in the allograft group and 12 recipients in the control group were analyzed. Histological assessment was performed in 5 of the recipients in each group, and microRNA expression was analyzed in the remaining recipients, except for 1 recipient in the syngeneic group. Results: In the allograft group, the relative microRNA‐146a expression was significantly higher in skin (2.34 ± 0.44) than in muscle (1.25 ± 0.22; p  = .034) and bone (1; p  = .0081). In the allograft group, microRNA‐155 expression was significantly higher in skin (1.91 ± 0.18) than in bone (1; p  = .010). Histological assessment showed that some skin tissue in the allograft group showed evidence of severe acute rejection. Conclusions: The microRNA‐146a and microRNA‐155 seemed to reflect the relative antigenicity during acute rejection of transplanted limbs. Skin seemed to be more antigenic than muscle and bone in both the histological assessment and gene expression analysis.